2021
DOI: 10.1098/rsos.200724
|View full text |Cite|
|
Sign up to set email alerts
|

The Godden and Baddeley (1975) experiment on context-dependent memory on land and underwater: a replication

Abstract: A replication of the experiment by Godden and Baddeley (Godden and Baddeley 1975 British Journal of Psychology 66 , 325–331 ( doi:10.1111/j.2044-8295.1975.tb01468.x )) on environmental context-dependent memory is described. Sixteen divers studied auditorily presented word lists on land or underwater and recalled these 4 min later on land or underwater (each diver participated in all four combinations). Contrary to the original study, we did not find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Context-dependent memory refers to the hypothesis that the higher the match between the context in which a memory is being retrieved and the context in which the memory was originally encoded, the more successful the recall is expected to be. In the abstract, Murre (2021) summarizes the results of the replication experiment as follows: “Contrary to the original experiment, we did not find that recall in the same context where the words had been learned was better than recall in the other context.” Does this suggest that the results of the original experiment were a false positive—as replication failures are commonly interpreted? There are many reasons to not jump at that conclusion including sampling error and the fact that the context of the replication was different from that of the original Godden and Baddeley (1975) experiment.…”
Section: Element-wise Openness and Assessing The Meaning Of Replicationsmentioning
confidence: 84%
See 3 more Smart Citations
“…Context-dependent memory refers to the hypothesis that the higher the match between the context in which a memory is being retrieved and the context in which the memory was originally encoded, the more successful the recall is expected to be. In the abstract, Murre (2021) summarizes the results of the replication experiment as follows: “Contrary to the original experiment, we did not find that recall in the same context where the words had been learned was better than recall in the other context.” Does this suggest that the results of the original experiment were a false positive—as replication failures are commonly interpreted? There are many reasons to not jump at that conclusion including sampling error and the fact that the context of the replication was different from that of the original Godden and Baddeley (1975) experiment.…”
Section: Element-wise Openness and Assessing The Meaning Of Replicationsmentioning
confidence: 84%
“…Another known boundary condition for the phenomenon is the outcome variable: Past research has shown that this works for retrieval tasks (e.g., free recall) and not recognition. The Murre (2021) replication did not carry over these contextual details and changed the design in a way to not instigate context-dependent memory. As a result, the differences between R and R′ become impossible to attribute to a single cause and fail to provide evidence that can confirm or refute the results of the original Godden and Baddeley (1975) experiment.…”
Section: Element-wise Openness and Assessing The Meaning Of Replicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A central question for all future research is whether inperson rather than on-line data collection is an essential auxiliary assumption for replication. The interested reader is also directed to Murre's (2021) recent failure to similarly replicate Godden & Baddeley's (1975) 'classic' finding of contextdependent memory between being on land and underwater. To Murre's (2021) credit, a number of auxiliary assumptions (of unknown importance) are noted in the attempted replication: the use of an indoor pool versus open water, the amateur or professional status of the divers, testing divers in a single day relative to across 4 days, to name but three.…”
Section: Experiments 8 (Rotate)mentioning
confidence: 99%